2018
DOI: 10.17261/pressacademia.2018.965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inertia and satisfaction on consumer loyalty in online shopping sites

Abstract: Purpose-This study deals with the effect of the required qualifications of an online shopping sites on consumer inertia and customer satisfaction and loyalty. Methodology-As a method of research, the convenience sampling method was preferred and face-to-face questionnaires were applied. Upon elimination of incomplete and incorrect questionnaires, 317 questionnaires were included in the evaluation. Findings-According to the results of the study, the adaptation, transaction ease and engagement which are dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In addition, customers' beliefs are essential in purchasing decisions from online shopping sites as they are based on perception, motivation, learning, and attitude (Akbar & James, 2014). Some studies have shown that customer perceptions are influenced by customer satisfaction, trust, and loyalty (Miller & Lammas, 2010;Chen & Chang, 2011;Eid, 2011;Chinomona & Sandada, 2013;Ercis et al, 2018;Ateş, 2018a). Critical factors for online customers include timely delivery, good customer support, good communication, secure payment, shopping methods, and an easy return process.…”
Section: Online Customer Loyalty and Customer Perceptionmentioning
confidence: 99%
“…In addition, customers' beliefs are essential in purchasing decisions from online shopping sites as they are based on perception, motivation, learning, and attitude (Akbar & James, 2014). Some studies have shown that customer perceptions are influenced by customer satisfaction, trust, and loyalty (Miller & Lammas, 2010;Chen & Chang, 2011;Eid, 2011;Chinomona & Sandada, 2013;Ercis et al, 2018;Ateş, 2018a). Critical factors for online customers include timely delivery, good customer support, good communication, secure payment, shopping methods, and an easy return process.…”
Section: Online Customer Loyalty and Customer Perceptionmentioning
confidence: 99%
“…Therefore, repeat purchases occur (Kuo et al, 2013). As a result, the probability of consumers switching brands is decreasing (Gray et al, 2017), and brand loyalty is being built (Yildiz, Deveci, & Ercis, 2018). This is because inertia tends to make consumers passive and adhere to the same pattern.…”
Section: Consumer Inertiamentioning
confidence: 99%